PREFERENSI GAYA BELAJAR MAHASISWA AKUNTANSI - Sulastri, Sri Pujiningsih, (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2010)
This study aims to find the differences between learning style preference in accounting students. Results of this research useful to determine teaching strategies, so itÂ can support improvement of student learning. Based on the analysis of test results using ANOVA can be concluded that there is no difference in student learning styles accountingÂ Â students. Learning style preferences of three groups of students is the same that is more like the learning style dependent. Keywords: Gaya Belajar, Strategi Mengajar.